Antibiotic exposure and development of necrotizing enterocolitis in very preterm neonates. Issue 4 (23rd November 2017) - Esmaeilizand, Rana; Shah, Prakesh S; Seshia, Mary; Yee, Wendy; Yoon, Eugene W; Dow, Kimberly; ,
Abstract: Objective: To examine the association between the duration of antibiotic exposure and development of stage 2 or 3 necrotizing enterocolitis (NEC) in very preterm neonates. Study Design: A retrospective case–control study was conducted from Canadian Neonatal Network data for preterm neonates born before 29 weeks' gestation and admitted 2010 through 2013. Efforts were made to match each NEC case to two controls for gestational age, birth weight (±100 g) and sex. Results: A total of 224 cases and 447 controls were identified. The incidence of antenatal steroid administration, the number of days nil-per-os and the number of antibiotic days prior to onset of NEC were significantly different in neonates with NEC. A multiple regression analysis revealed that the duration of antibiotic use was higher among NEC cases compared to controls (P<0.01). Empiric antibiotic treatment of 5 or more days was associated with significantly increased odds of NEC as compared with antibiotic exposure of 0 to 4 days (adjusted odds ratio: 2.02; 95% CI 1.55, 3.13). Conclusion: Empiric antibiotic exposure for 5 or more days in preterm neonates born before 29 weeks' gestation was associated with an increased risk of NEC.